The Impact of Coping Strategies and Perceived Family Support on Depressive and Anxious Symptomatology During the Coronavirus Pandemic (COVID-19) Lockdown - Mariani, Rachele; Renzi, Alessia; Di Trani, Michela; Trabucchi, Guido; Danskin, Kerri; Tambelli, Renata (Frontiers in Psychiatry, 2020)
The coronavirus pandemic represents a severe global crisis, affecting physical and psychological health. Lockdown rules imposed to counteract the rapid growth of COVID-19, mainly social restrictions, have represented a risk factor for developing depressive and anxious symptoms. The research aims are to explore the effect of coping strategies and perceived social support on depressive and anxious symptomatology during the COVID-19 pandemic. Ninety-six healthy people (46 males, mean age = 39.3; SD = 16.6) completed through on-line platform: Socio-demographic questionnaire, Coping Inventory for Stressful Situations (CISS), Multidimensional Scale of Perceived Social Support (MSPSS) and Symptom Checklist-90-Revised (SCL-90-R), three weeks after the imposition of lockdown restrictions. SCL-90-R Depression scores showed significant positive correlation with CISS Emotion (r = .85; p =.001) and Avoidant (r = .34; p = .018), a significant negative correlation with MSPSS Family support (r = -.43; p = .003). SCL-90-R Anxiety scores showed a significant positive correlation with CISS Emotion (r =.72; p = .001) and Avoidant (r = .35; p = .016). No significant correlations between both CISS Emotion and Avoidant scales with social support emerged. Two Multiple Linear Regression analysis were performed using respectively SCL-90-R Depression and Anxiety scores as dependent variables, and the CISS and MSPSS scales, age and gender as predictors. The first regression model (R2 = .78; adjusted R2 = .75) revealed CISS Emotion (β = .83; p = .001) and MSPSS Family support (β = -.24; p = .004) had a predictive effect on SCL-90-R Depression scores. The second regression model (R2 = .52; adjusted R2 = .472) revealed that only CISS Emotion (β = .71; p = .001) predicted the SCL-90-R Anxiety scores. In conclusion, during the COVID-19 pandemic lockdowns, coping focus on emotions seemed to increase anxious and depressive symptoms, probably due to the uncontrollable nature of the stressful event and the high emotional response. Family support which reduces the sense of loneliness had an exclusive role in mitigating depressive symptoms. These results highlight the importance of promoting psychological strategies to improve emotional regulation skills, reducing isolation from family, to prevent mood symptomatology in healthy citizens during large-scale health crises.